Effects of Personal Social Capital on the Isomorphism of Stricto Sensu Graduate Courses - Meier de Carvalho Albano, Leandro; Popadiuk, Silvio (Administração (São Paulo), 2024)
This research investigates whether personal social capital influences institutional isomorphism. Two premises were considered: i) neo-institutional theory and institutional isomorphism provide tools for explaining the homogenization of practices and structures between organizations and ii) personal social capital in organizations contributes to institutional isomorphism. The study was developed in two aspects — one theoretical and the other empirical — which made it possible to corroborate the proposed hypothesis. Quantitative research methods were used in the empirical aspect, with a sample of 176 coordinators of stricto sensu postgraduate courses. Higher education institutions (HEIs) were evaluated in two facets: i) organizations subject to isomorphic phenomena, such as firms from other sectors, and ii) responsibility for the perpetuation of these processes, from the training of teachers (who will become masters of future managers) and the knowledge they generate. At the end of the research, it was confirmed that personal social capital has a positive effect on institutional isomorphism through the internal relations of the coordinators. The manifestations of coercive, normative, and mimetic isomorphisms in the HEIs were also identified.